Pollination-driven modulation of amino acid biosynthesis in plum: A multi-omics approach - Lijun Deng; Binshu Yuan; Xiaojun Jin; Yingying Xu; Yuhuan Feng; Xuan Zhang; Hui Zhang; Bo Xiong; Xun Wang; Guochao Sun; Mingfei Zhang; Siya He; et al. (Journal of Agriculture and Food Research, 2025)
Plum is a popular fruit worldwide, possessing a rich nutritional profile. In agronomic practices, different pollen sources can influence fruit metabolites. However, few studies have been conducted on the effects of various pollinated cultivars on amino acid biosynthesis in plum fruit. In this study, ‘Fengtang’ plum was artificially pollinated using pollen from ‘Fenghuang’ plum and ‘Yinhong’ plum. The resulting fruit groups derived from ‘Fenghuang’ and ‘Yinhong’ pollination were designated as FF and FY, respectively. Subsequently, we performed metabolomic and transcriptomic analyses of these fruits. The results showed that the total amino acid content in FF was significantly higher than that in FY throughout the fruit development period. A total of 191 amino acids (AAs) and their derivatives were identified by metabolome, including eight essential AAs. Among them, L-leucine, L-isoleucine, and L-phenylalanine were particularly abundant. Moreover, pollen sources induced variations in the levels of 58 AAs between FF and FY fruits. Nine key genes and 46 transcription factors (TFs) significantly influencing amino acid biosynthesis in ‘Fengtang’ plum were identified through redundancy analysis (RDA) and weighted gene co-expression network analysis (WGCNA). The findings underscore the potential to improve the nutritional value of plums through the strategic selection of pollination cultivars. In addition, this research provides a foundation for a deeper understanding of the regulatory mechanisms underlying amino acid biosynthesis in plum and supports the development of relevant functional foods.